Pangempon Pura Pajinengan Gunung Tap Sai Kabupaten Karangasem – Bali, untuk Desain Konservasi Mandala Pura - I Wayan Runa; I Nyoman Warnata; I Nyoman Nuri Arthana Nuri Arthana (Universitas Warmadewa, 2021)
Pura Pajinengan Mount Tap Sai is located in Puragai Hamlet, Besakih Traditional Village, Pempatan Village, Rendang District, Karangasem Regency - Bali, hereinafter referred to as Pura Tap Sai. Tap Sai Temple is located on the northwest slope of Mount Agung. People who Tangkil come to the temple to ask for safety and grace. Tap Sai comes from the word matapa sai sai (daily meditation or meditation). On the main page (utamaning mandala) of Pura Tap Sai, there is also a shrine of the Lingga Yoni wrapped in tree roots (natural) which the people believe is a place to ask for children or offspring, mate, all health problems, ask for medicine, and also fortune. After praying at the main mandala, each devotee / pemedek will be given a bundle (11) of incense to make a special wish at the natural Yoni Lingga. The existence of this temple is in the middle of the forest so that the natural atmosphere is calm, peaceful, and sacred. Therefore, this temple is also a public attraction both for spiritual activities and for traveling. With the increasing number of community members visiting Pura Pajinengan Mount Tap Sai, it is necessary to organize the main temple's mandala so that it is able to accommodate the number of visitors optimally and of course it is also safe for people with disabilities, given the high condition of the temple mandala such as terraces due to the contours of the ground. that's tilted. Based on the above problems, the method of implementation is through the design of the mandala pura conservation. Data collection was in the form of exploration to Pajinengan Temple Mount Tap Sai to obtain data in the design process. The design of the temple mandala to be more unique or distinctive, including the design of buildings and pelinggih and circulation materials for people with disabilities. In addition, it also conducted opinion polls and socialization to optimize the design of the mandala conservation at Pura Pajinengan Mount Tap Sai. The final output in the first year of the Community Partnership Program or this service for the community of Pajinengan Temple Mount Tap Sai people is preliminary data for the design of the mandala and temple shrine conservation. The preliminary data consist of the area of ​​land / temple area, the area of ​​the temple mandala, the existing main palinggih buildings, the existing supporting palinggih buildings, the sacred trees that need to be preserved, and the unique potential for the concept of temple development.